High throughput detection of antibiotic residues in milk by time-resolved fluorescence immunochromatography based on QR code. Issue 9 (1st September 2020) - Ashuo, Asha; Zou, Wenjia; Fu, Jingjie; Yang, Tengkun; Yu, Linlin; Liu, Wei; Yang, Liu; Mari, Ghulam Mujtaba; Jiang, Haiyang
ABSTRACT: Herein, we have successfully established a novel, rapid, and simple lateral-flow immunoassay based on time-resolved fluorescence and biotin-streptavidin to detect the residues of various antibiotics in milk. The fluorescence signal and sensitivity of immunochromatography were enhanced through biotinylated antibody coupled with streptavidin europium microspheres. Moreover, due to the use of a QR Code and fluorescent reader, quantitative detection and real-time data uploading can be achieved. Under the optimal conditions, the various antibiotic residues were detected in the milk samples. The results showed that the limits of detection of tylosin, lincomycin and doxycycline were 0.10, 0.06, and 0.27 ng/mL, respectively. The recoveries of the spiked milk samples were 88.9%~127%, with coefficients of variation less than 11%, and the test strip can be stored at room temperature for 12 months. This study shows that the proposed time-resolved fluorescence immunoassay is sensitive, rapid and reliable, and has the potential to be used for detection of veterinary antibiotic residues in food safety fields.